Economics of Rural Infraestructure: Evaluating the Provision of Transport and Electricity in Peru - Aguirre Montoya, Julio César (2016)
Using a unique governmental database from Peru, I find that electoral cycles significantly affect the hazard of renegotiation of transport infrastructure concession contracts. The effect of electoral cycles remains robust when applying a varied set of specifications. In addition, electoral cycles have positive marginal effects on the hazard of renegotiation of concession contracts between 3% and 6%. These results provide a perspective on the importance of enforcing institutional and regulatory supervisory activities of infrastructure concession contracts in order to minimize possible political influences on the contractual stability of these contracts.